Detection of Bacterial DNA in the Plasma of Psoriasis Patients and its Association with Serum Intestinal Fatty Acid Binding Protein Concentration - Samah Ali Abd, Jinan Mj Alsaffar, Alice K. Agop, Entissar Jawad Kadhem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There is evidence of the role of microorganisms, in particular in the throat and skin in psoriasis pathogenesis. This study aimed to investigate the presence of bacterial DNA (bacDNA) in patients' plasma and its association with gut barrier integrity . Methodology: Plasma was collected from 60 psoriasis patients in the flare up stage and 40 healthy controls. BacDNA was detected by PCR amplification using a 16S ribosomal DNA primer. The amplified DNA fragments were then sequenced to determine their bacterial origin. Results: Bacterial DNA was detected in 51 of 60 patients and only in 4 of 40 healthy controls. BacDNA sequencing results revealed that these bacterial species originated from the gut and skin. On the other hand, intestinal fatty acid binding protein (I-FABP) was measured by ELISA technique to investigate the integrity of the intestinal barrier. Serum concentrations of I-FABP were significantly higher in psoriasis patients compared with the healthy group and were positively correlated with the presence of bacDNA in patients' plasma. Conclusion: These findings suggest that psoriasis flare up is associated with translocation of bacteria and its metabolites into the blood stream, causing an immune system response. The specific mechanism of bacDNA in the pathogenesis of psoriasis needs to be comprehensively studied.